EVALUATING THE EFFECTIVENESS OF A NOVEL MULTIMODAL TREATMENT FOR AVASCULAR NECROSIS OF THE HEAD OF FEMUR OF POST COVID ETIOLOGY: A RETROSPECTIVE COHORT STUDY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Avascular necrosis (AVN) of the femoral head results from impaired blood supply, a condition increasingly observed in post-COVID-19 patients due to virus-induced microvascular damage. Conventional therapies often fail to address the vascular pathology. This retrospective cohort study, conducted from September 2020 to March 2024 in a tertiary hospital in Uzbekistan, included 350 post-COVID AVN patients divided into two groups. The case group (n=190) received standard conservative treatment plus hirudotherapy (2–3 times/week for 2 months), while the control group (n=160) received standard conservative care alone. Outcomes were evaluated through MRI staging and SF‑36 scores at baseline and every 6 months over 2 years. Results showed a significantly lower rate of femoral head collapse (10% vs. 34.4%), progression (20% vs. 51.3%), and surgery (3.2% vs. 10%) in the case group, with improved SF‑36 scores. This multimodal therapy demonstrates potential as an effective, non-surgical option for managing early-stage post-COVID AVN.